Endoscopic Extraction of CBD Stone: single centre experience in tertiary care centre - Gnawali, Arun; Pathak, Rahul; Pandey, Rajesh; Khadga, Prem Krishna; Sharma, Sashi; Jha, Anurag; Hamal, Rabin; Koirala, Dinesh (Journal of Advances in Internal Medicine, 2020)
Background and Aims: Introduction: Endoscopic Retrograde Cholangiopancreatography(ERCP) has become the first line treatment for patients with common bile duct (CBD) stones. This technique may fail, however, due to presence of a large stone, multiple stones, periampullary diverticula or CBD stricture. The aim of this study was to evaluate the success of CBD cannulation, Endoscopic Sphincterotomy(EST) and CBD clearance in initial attempt, identify the failures of stone extraction and assess the post-ERCP complications. Methods: A prospective study was carried out over the period of January 2019 to January 2020 on 100 consecutive patients with CBD stones. ERCP was done and the stone size and number recorded. EST was performed using a diathermy unit with a cutting current and stones were extracted using a Balloon catheter or a Dormia basket. Results: Of the 100 patients, 44 were male and 56 were female with mean age of 52}17years. Selective CBD cannulation and cholangiogram was achieved in 90%, EST was successful in 90% and complete stone clearance was achieved in first attempt in 46 patients (59%). 52 patients had difficult CBD stone. There were nine complications, most of which rapidly resolved on conservative treatment (four post-ERCP pancreatitis, three bleeding and one retroperitoneal perforation) and one mortality in an old lady due to PSVT that couldn’t be directly attributed to ERCP. Among patients with Stone less than 15 mm in diameter(n=58), stone was removed successfully in 45 patients(78%) whereas in patients with stones over 15 mm (n=20) only one was removed successfully (5%) at initial attempt. Of these 32 patients with residual stones, 13 were referred for surgery and 19 had insertion of biliary stent to be followed by repeat ERCP. Conclusion: Endoscopic therapy is a simple, effective and safe method of treatment in patients with CBD stone.